On the modeling of a dissolved iron removal from underground water by filtration - Polyakov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
A nonlinear task of Fe2+ transfer and transformation (adsorption and oxidation) within the porous layer of a rapid filter is posed and solved exactly. The dependences for Fe2+ concentrations which are given in the implicit parametric form are illustrated by examples of calculating the changes in time and height of its dissolved form content. An approximate solution to the task was obtained in the explicit form using the iteration procedure to study the dynamics of Fe3+ and total Fe in future. The last solution exhibited in the calculations of filtration characteristics has an error under 1 %.